The Effectiveness of Guided Discovery Learning Model for The Skills of Inquiry, Metacognition Skills, And Cognitive Learning Outcome of Students Grade 8 MTsN Panglungan - Herry Cahya Kurniawan; Febriana Irawati; Poppy Rahmatika Primandiri; Agus Muji Santoso (Universitas Sebelas Maret, 2015)
The purpose of the research was to determine the effectiveness of guided discovery learning model for the skills of inquiry, metacognition skills, and results of cognitive learning outcome of students. The research was non-equivalent control group design in the eighth grade students of MTsN Panglungan Jombang conducted on 12th until 25th May, 2015. Some instruments to support this study were the instrument of inquiry skills which consisted of rubric of learning process and product, assessment of metacognition skills in the form of initial and final test integrated with the cognitive achievement test, and measurement of students’ cognitive learning outcomes using essay test. Data were tabulated and analysed by t- test independent using the SPSS16 program for windows 2007. This research showed that: (1) there were differences in the skills of inquiry process between the control and the treatment group (α = 0.01 <0.05), (2) there was a difference between the product of inquiry skills (α = 0.015 <0.05 ), (3) metacognition skills in the experimental class and the class dick final test results indicate that there were significant differences grade between control and treatment (α = 0.040 <0.05), (4) results of students’ cognitive final test indicated that there was a significant difference from the control and treatment (α = 0.003 <0.05). It can be concluded that guided discovery learning model can improve the skills of inquiry processes and products, metacognition skills, and results of students’ cognitive learning.Keywords: guided discovery, inkuri skills, metacognition skills, results of cognitive learning